Waiting for spring. 14 - Anashin, 1992- (Kodansha Comics, 2021)
"Mitsuki and Towa have found true love, leaving Rui to despair about his own future romance! However, in the background, Kyōsuke has been having his own girl problems -- will his first love return his affection? Meanwhile, Nanase and Ryūji bump into their own relationship issues, and Aya must cope with his heartbreak once more. FINAL VOLUME!"--Amazon.